"They're Everywhere!": Symbolically Threatening Groups Seem More Pervasive Than Nonthreatening Groups. (June 2022) - Ponce de Leon, Rebecca; Rifkin, Jacqueline R.; Larrick, Richard P.
The meaning of places is socially constructed, often informed by the groups that seem pervasive there. For instance, the University of Pennsylvania is sometimes pejoratively called "Jew-niversity of Pennsylvania, " and the city of Decatur, Georgia, is disparagingly nicknamed "Dyke-atur, " connoting the respective pervasiveness of Jewish students and gay residents. Because these pervasiveness perceptions meaningfully impact how people navigate the social world, it is critical to understand the factors that influence their formation. Across surveys, experiments, and archival data, six studies ( N = 3, 039 American adults) revealed the role of symbolic threat (i.e., perceived differences in values and worldviews). Specifically, holding constant important features of the group and context, we demonstrated that groups higher in symbolic threat are perceived as more populous in a place and more associated with that place than groups lower in symbolic threat. Ultimately, this work reveals that symbolic threat can both distort how people understand their surroundings and shape the meaning of places.